Learning outcomes and assessment methodology: Case study of an undergraduate engineering project. Issue 2 (April 2019) - Naqvi, Syed Rameez; Akram, Tallha; Haider, Sajjad Ali; Khan, Wilayat; Kamran, Muhammad; Muhammad, Nazeer; Nawaz Qadri, Nadia
Considering the effectiveness of outcome-based education and its increasing implementation in higher education, we propose a set of course learning outcomes that may be related to any engineering problem, in particular the final year project in undergraduate engineering programs. We also show how these outcomes may be mapped to program learning outcomes identified by the Washington Accord. Our case study is an embedded vision system developed by our own group, which we assess against these outcomes using the proposed self-assessment report rubrics. We conclude by presenting assessment reports for our project from two expert academics showing how well it managed to attain the course learning outcomes. This work is intended to give students a direction to professionally as well as ethically approach a particular design problem, and at the same time help the instructors evaluate their students' projects by simply adopting the proposed assessment methodology.